Crosstalk in stereoscopic displays: A review - Woods, Andrew J. (International Society for Optical Eng/Society for Imaging Science and Technology, 2012)
Crosstalk, also known as ghosting or leakage, is a primary factor in determining the image quality of stereoscopic three dimensional (3D) displays. In a stereoscopic display, a separate perspective view is presented to each of the observer’s two eyes in order to experience a 3D image with depth sensation. When crosstalk is present in a stereoscopic display, each eye will see a combination of the image intended for that eye, and some of the image intended for the other eye—making the image look doubled or ghosted. High levels of crosstalk can make stereoscopic images hard to fuse and lack fidelity, so it is important to achieve low levels of crosstalk in the development of high-quality stereoscopic displays. Descriptive and mathematical definitions of these terms are formalized and summarized. The mechanisms by which crosstalk occurs in different stereoscopic display technologies are also reviewed, including micropol 3D liquid crystal displays (LCDs), autostereoscopic (lenticular and parallax barrier), polarized projection, anaglyph, and time-sequential 3D on LCDs, plasma display panels and cathode ray tubes. Crosstalk reduction and crosstalk cancellation are also discussed along with methods of measuring and simulating crosstalk.